Analysis of the Concepts on Game Rides at Atlantis Island Surabaya - Fifta Itsna Iftirani; Nadila Wahyu Pertiwi; Via Aprilia Nugraha; Binar Kurnia Prahani; Dwikoranto (Studies in Philosophy of Science and Education, 2021)
Physics learning that seems boring makes physics lessons more fun if packaged in the form of games and combined with physics concepts. The purpose of this research is to find out the rides on Atlantis Island Surabaya that use the application of physics concepts. This research used a descriptive method with descriptive analysis. Data was collected by making direct observations or observations on the rides at Atlantis Island Surabaya and linking them to physics concepts. The results showed that several rides at Atlantis Island Surabaya use physics concepts in their performance, including power surge, dark coaster, wave swinger, globe of death, viking, and spilled bucket. The rides use physics concepts such as circular motion, rotational motion, kinematic motion, parabolic motion, action-reaction, centrifugal force, centripetal force, potential energy, kinetic energy, and discharge.